2016
DOI: 10.1038/ncomms10442
|View full text |Cite
|
Sign up to set email alerts
|

Self-renewal of CD133hi cells by IL6/Notch3 signalling regulates endocrine resistance in metastatic breast cancer

Abstract: The mechanisms of metastatic progression from hormonal therapy (HT) are largely unknown in luminal breast cancer. Here we demonstrate the enrichment of CD133hi/ERlo cancer cells in clinical specimens following neoadjuvant endocrine therapy and in HT refractory metastatic disease. We develop experimental models of metastatic luminal breast cancer and demonstrate that HT can promote the generation of HT-resistant, self-renewing CD133hi/ERlo/IL6hi cancer stem cells (CSCs). HT initially abrogates oxidative phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
149
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(159 citation statements)
references
References 26 publications
8
149
1
1
Order By: Relevance
“…Interestingly, we show that IL-6, one of the known targets genes of NF-κB, is potently downregulated by the inhibitors. IL-6 has been recently linked to cancer stemness in multiple cancer models (Sansone et al, 2016; van der Zee et al, 2015). The exact mechanism by which NF-κB is inactivated by desaturase inhibitors in CSCs remains undefined.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we show that IL-6, one of the known targets genes of NF-κB, is potently downregulated by the inhibitors. IL-6 has been recently linked to cancer stemness in multiple cancer models (Sansone et al, 2016; van der Zee et al, 2015). The exact mechanism by which NF-κB is inactivated by desaturase inhibitors in CSCs remains undefined.…”
Section: Discussionmentioning
confidence: 99%
“…A recent preclinical study by Sansone et al (2016) found that chronic hormone therapy of mice with ER-positive luminal breast cancer led to induction of a dormant, CD133 high /ER low /mitochondria low population of cells, which produced IL-6 in an autocrine manner. These cells showed an increase in pluripotency genes and were able to exit dormancy by utilizing IL-6/Stat3/Notch3-driven, ER-independent self-renewal and mitochondria reactivation.…”
Section: Reactivation From Dormancymentioning
confidence: 99%
“…These cells showed an increase in pluripotency genes and were able to exit dormancy by utilizing IL-6/Stat3/Notch3-driven, ER-independent self-renewal and mitochondria reactivation. The use of an anti-IL6R antibody restored ER expression in HT-resistant cells and double treatment with HT/anti-IL6R antibodies in vivo was effective even in HT-resistant tumors (Sansone et al, 2016). These results demonstrate that dormancy may be induced by therapy and that microenvironment-derived cytokines such as IL-6 may be able to reawaken dormant cells.…”
Section: Reactivation From Dormancymentioning
confidence: 99%
“…The acquisition of resistance manifests with a partial epithelial-mesenchymal transition (EMT) and increased migratory and invasive activity both in anti-estrogen-resistant cell line models (14) and in clinical samples (14)(15)(16)(17). Furthermore, a subset of tumor-initiating cells with stem-like characteristics (cancer stem cells: CSCs) is enriched in tamoxifen-resistant breast cancers and may demonstrate resistance to endocrine therapies, thus contributing to disease recurrence and metastatic progression (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%